PENDAMPINGAN PROGRAM KAMPUS MENGAJAR ANGKATAN 2 DI SD DYNATA DENPASAR PROVINSI BALI - I Gusti Ayu Mahatma Agung (Jurnal Abdi Insani, 2022)
Online learning is widely applied in schools in Indonesia during the Covid-19 pandemic. Teachers and students are expected to adapt to the use of technology in learning. However, there are many obstacles in the implementation of online learning. Obstacles that often occur during the online learning process are the lack of digital literacy, unstable internet connections, availability of devices, and limited quotas. It has caused a negative impact on students’ motivation and understanding, especially at the elementary level. The Teaching Campus program aims to assist the learning process in schools affected by Covid-19, especially in literacy and numeracy. In addition, this program is expected to foster university student leadership. The Campus Teaching Batch 2 Program was carried out by five university students under the supervision of a lecturer. This program has been conducted for twenty weeks at SD Dynata Denpasar. School observation was carried out at the beginning of the program as a reference in preparing work programs. The university students collaborated with the teachers in literacy and numeracy learning during the program, both online and offline. In August and September 2021, all learning activities at SD Dynata Denpasar were conducted online through Google Meet. Literacy and numeracy activities were adjusted to the sub-themes in the thematic books. In addition to teaching assistance, the university students also helped the teachers in technology adaptation and administration. The university students also helped the school in limited face-to-face learning, which was held in October 2021. The university students assisted the teachers and ensured the implementation of health protocols in the school. Through this program, the school was assisted in the implementation of online and offline learning. The ability of the university students to communicate and collaborate has also increased.